The Role of Law Enforcement Officials in Implementing Alternative Dispute Resolution in Traffic Accident Cases in Indonesia - Serimin Pinem; Iyllyana Che Rosli (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study analyzes the role of law enforcement officials in implementing Alternative Dispute Resolution (ADR) in traffic accident cases in Indonesia. Although traffic accidents are generally processed through formal criminal justice mechanisms, many cases involve negligence and minor harm, making restorative settlement more appropriate. This research applies an empirical juridical (socio-legal) approach with a qualitative descriptive-analytical design. Data were collected through interviews, observations, and document analysis, and examined using qualitative analysis with triangulation. The findings indicate that law enforcement officials, particularly the police, act as facilitators, mediators, legal educators, and process controllers in promoting peaceful settlements. ADR is conducted through several stages, including initial case assessment, offering mediation, facilitating dialogue, drafting agreements, and monitoring compliance. In exercising discretion, officials consider the severity of the accident, the element of fault, the perpetrator’s attitude, the victim’s consent, and social benefits. However, implementation faces challenges such as the absence of standardized procedures, limited mediation skills, low public legal awareness, and concerns over transparency. Strengthening regulatory guidance and institutional capacity is essential to ensure fair and humane dispute resolution.